2012 2nd International Conference on Consumer Electronics, Communications and Networks (CECNet) 2012
DOI: 10.1109/cecnet.2012.6201878
|View full text |Cite
|
Sign up to set email alerts
|

SM2 cryptographic algorithm based on discrete logarithm problem and prospect

Abstract: with the development of technology, network has become an integral part of the life. At the same time the protection to network information is becoming very important. Encryption is one of the most effective ways to protect the information. The sender will symmetrically encrypt and send the data through the network, and receiver will decrypt the information to get the plaintext. All of information in network has been encrypted. The symmetric key will be the most effectively distributed through asymmetrical key… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…SM2 Signature Algorithm. The SM2 algorithm is an asymmetric encryption algorithm introduced by the China National Cryptography Administration in 2010 [33]. It is aimed at replacing the widely employed 1024-bit RSA algorithm.…”
Section: Interplanetary File System (Ipfs) the Interplanetarymentioning
confidence: 99%
“…SM2 Signature Algorithm. The SM2 algorithm is an asymmetric encryption algorithm introduced by the China National Cryptography Administration in 2010 [33]. It is aimed at replacing the widely employed 1024-bit RSA algorithm.…”
Section: Interplanetary File System (Ipfs) the Interplanetarymentioning
confidence: 99%
“…Bai et al [12] did a theoretical comparative study of SM2 and the international standard ECC algorithm (which seems to refer to ECDSA, although this is not clearly mentioned), with regards to efficiency and security. They concluded that the SM2 algorithm is better than the international standard ECC algorithm, because the SM2 signature covers ECC parameters that can be used to verify the correctness of the plaintext.…”
Section: Related Workmentioning
confidence: 99%